Relationship between Father's Cheating Behavior and Son's Cheating Behavior - Alexander; Rizky, Muhammad (Caring : Jurnal Keperawatan, 2025)
This research aims to investigate the relationship between fathers' cheating behavior and sons' cheating behavior tendencies. Social learning theory states that behaviors observed in parents can serve as models for children in developing their own behaviors, including in the context of romantic relationships. This study used a quantitative approach with a survey design involving 384 adult male respondents. Measurements were made using validated scales, such as the Infidelity Scale (IS) by Drigotas et al. (1999) to assess individual tendencies to commit infidelity and the Perceived Parental Infidelity Scale adapted from the Parental Marital Conflict Scale (Buehler & Gerard, 2002). Data analysis was conducted using Pearson correlation technique to determine the relationship between father's infidelity behavior and son's infidelity behavior. The results showed a significant positive relationship (r = 0.45, p < 0.01), meaning that the higher the level of father's involvement in infidelity, the more likely sons are to show similar tendencies in their own relationships. The implications of these findings suggest the need for a more in-depth psychosocial approach in understanding the factors that influence cheating behavior, especially in an intergenerational context. By understanding how family experiences shape individuals' romantic behavior patterns, family-based interventions and emotional education can be developed to prevent the cycle of infidelity in relationships.